2008
DOI: 10.1016/j.poly.2008.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Bis-tridentate chelates of an asymmetric ligand: X-ray structures and solution NMR characterization of divalent zinc triad metal ion complexes of N-(2-pyridylmethyl)-N-(2-(methylthio)ethyl)amine

Abstract: Divalent zinc triad metal ion complexes of type M(L)(2)(ClO(4))(2) (L = N-(2-pyridylmethyl)-N-(2-(methylthio)ethyl)amine) with N(4)S(2) metal coordination spheres were isolated and characterized by X-ray crystallography and variable temperature proton NMR. Although bis-tridentate chelates have nine geometric isomers, the crystallographically characterized complexes of all three metal ions had trans facial octahedral coordination geometry with C(i) symmetry. Despite the low coordination number and geometric pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…Interestingly, significant broadening at cryogenic temperatures suggests the rate of an intramolecular isomerization process was approaching the chemical shift time scale. However, intramolecular isomerization does not preclude detection of J(M 1 H) [6,7,17]. Proton NMR spectra in alternative solvents were comparable, suggesting negligible solvent involvement in solution equilibria.…”
Section: Crystal Structures Of 1:1 Metal To Ligand Complexesmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, significant broadening at cryogenic temperatures suggests the rate of an intramolecular isomerization process was approaching the chemical shift time scale. However, intramolecular isomerization does not preclude detection of J(M 1 H) [6,7,17]. Proton NMR spectra in alternative solvents were comparable, suggesting negligible solvent involvement in solution equilibria.…”
Section: Crystal Structures Of 1:1 Metal To Ligand Complexesmentioning
confidence: 93%
“…Complexes of diamagnetic zinc triad metals are readily amenable to characterization by NMR, which can often be used to detect coordination equilibria. Although zinc does not have an isotope with favorable NMR properties, previous studies have revealed slow inter-and intramolecular ligand exchange on the NMR chemical shift time scale for zinc triad complexes of multidentate ligands [6]. For Cd(II) and Hg(II) complexes; slow exchange on the typically shorter J( 111/113 Cd 1 H) and J( 199 Hg 1 H) time scales, respectively, may also be observed.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other interesting cases include the work of Butcher et al [55,56] where Zn-S distances of 2.50 and 2.60 Å were found.…”
Section: The Zn-s(thioether) Bond Lengths In Coordination Compoundsmentioning
confidence: 99%
“…1-(Pyridin-2-yl)-N-((pyridin-2-yl)methyl)ethanamine (10a): 16 N-(Pyridin-2-yl)-N-((pyridin-2-yl)methyl)benzamide (14). The precursor amine 14a was synthesized by the general procedure a described above.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%